3(t+2)+4(t-1)=72

Simple and best practice solution for 3(t+2)+4(t-1)=72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(t+2)+4(t-1)=72 equation:


Simplifying
3(t + 2) + 4(t + -1) = 72

Reorder the terms:
3(2 + t) + 4(t + -1) = 72
(2 * 3 + t * 3) + 4(t + -1) = 72
(6 + 3t) + 4(t + -1) = 72

Reorder the terms:
6 + 3t + 4(-1 + t) = 72
6 + 3t + (-1 * 4 + t * 4) = 72
6 + 3t + (-4 + 4t) = 72

Reorder the terms:
6 + -4 + 3t + 4t = 72

Combine like terms: 6 + -4 = 2
2 + 3t + 4t = 72

Combine like terms: 3t + 4t = 7t
2 + 7t = 72

Solving
2 + 7t = 72

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 7t = 72 + -2

Combine like terms: 2 + -2 = 0
0 + 7t = 72 + -2
7t = 72 + -2

Combine like terms: 72 + -2 = 70
7t = 70

Divide each side by '7'.
t = 10

Simplifying
t = 10

See similar equations:

| 16+6z=-8 | | 3log^7x=9 | | -25y^2-60y+60= | | d/33 | | -109/3 | | F(x)=4x^2-24x+20 | | t/4-7=16 | | 6x+7=-48-5x | | x^2-2.8x=9 | | 3s-15=-15 | | 5x^2-9x-7=0 | | x/4=21/36 | | -8+5t=-6 | | 7+91x=52x+16 | | 40-2x=8-10x | | 1/2/5/4 | | 8m+6=28 | | 3x+100=8x-5 | | -4(2t+10)=-8 | | x^2+10x-25=3x+5 | | -10(s+4)=-111 | | 6x^4-216=0 | | -4(3x+9)=-12x+36 | | 5-4X=1/2 | | 12-2y(y)=10 | | 3(f-9)=-42 | | 5+7x(9-2)+14= | | xsquared-2.8x=9 | | 1/2(2a-4b | | 4+30x=20x+20 | | 400/100 | | 2y+4y+3y+5y+6+18= |

Equations solver categories